2020
DOI: 10.1109/access.2020.3028395
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and Rapid Traffic Congestion Detection Approach Based on Deep Residual Learning and Motion Trajectories

Abstract: Traffic congestion detection systems help manage traffic in crowded cities by analyzing videos of vehicles. Existing systems largely depend on texture and motion features. Such systems face several challenges, including illumination changes caused by variations in weather conditions, complexity of scenes, vehicle occlusion, and the ambiguity of stopped vehicles. To overcome these issues, this paper proposes a rapid and reliable traffic congestion detection method based on the modeling of video dynamics using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As part of the quality verification of the license plate recognition subsystem, it was determined that the installed fixed point cameras show high reliability of almost above 95% when using two cameras and 90% when using one camera. The reliability values are absolutely sufficient for systems of similar type, as also evidenced by publications focusing on tests by other authors [22][23][24][25]. In general, it is advisable to place the cameras with license plate detection as close as possible to the communication.…”
Section: Discussionmentioning
confidence: 83%
“…As part of the quality verification of the license plate recognition subsystem, it was determined that the installed fixed point cameras show high reliability of almost above 95% when using two cameras and 90% when using one camera. The reliability values are absolutely sufficient for systems of similar type, as also evidenced by publications focusing on tests by other authors [22][23][24][25]. In general, it is advisable to place the cameras with license plate detection as close as possible to the communication.…”
Section: Discussionmentioning
confidence: 83%
“…Nguyen et al [5] proposed a face recognition method that combines a learning framework. M. Hori et al [6] identified a major challenge of facial recognition as the large appearance variations caused by factors such as viewpoints.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, depending solely on one feature has its shortcoming. In our previous work [17], a congestion classification was achieved by aggregating the output from separate motion-based and texture-based classifiers. Motion features were generated by averaging motion trajectories every batch of frames, while the texture features were obtained by generating compact texture vectors using the learning-to-rank technique [18].…”
Section: Related Workmentioning
confidence: 99%